Talking about Medicine ESP Book 2 - Tenelanda, Dennys (2020)
-- Heart -- Pancreas -- Liver -- Lungs -- Stomach -- Masculine reproductive system -- Female reproductive system -- An emergency -- The physical examination and health assessment -- A surgery -- Physical examination of the abdomen -- Pulmonary examination